Phylogeography of the parasitic mite Laelaps agilis in Western Palearctic shows lineages lacking host specificity but possessing different demographic histories - Nazarizadeh, Masoud; Martinů, Jana; Nováková, Milena; Stanko, Michal; Štefka, Jan (BMC zoology, 2022)
BACKGROUND: Laelaps agilis C.L. Koch, 1836 is one the most abundant and widespread parasitic mite species in the Western Palearctic. It is a permanent ectoparasite associated with the Apodemus genus, which transmits Hepatozoon species via the host's blood. Phylogenetic relationships, genealogy and host specificity of the mite are uncertain in the Western Palearctic. Here, we investigated the population genetic structure of 132 individual mites across Europe from their Apodemus and Clethrionomys hosts. Phylogenetic relationships and genetic variation of the populations were analyzed using cytochrome c oxidase subunit I (COI) gene sequences. RESULTS: We recovered three main mtDNA lineages within L. agilis in the Western Palearctic, which differentiated between 1.02 and 1.79 million years ago during the Pleistocene period: (i) Lineage A, including structured populations from Western Europe and the Czech Republic, (ii) Lineage B, which included only a few individuals from Greece and the Czech Republic; and (iii) Lineage C, which comprised admixed populations from Western and Eastern Europe. Contrary to their population genetic differentiation, the lineages did not show signs of specificity to different hosts. Finally, we confirmed that the sympatric congener L. clethrionomydis is represented by a separated monophyletic lineage. CONCLUSION: Differences in the depth of population structure between L. agilis Lineages A and C, corroborated by the neutrality tests and demographic history analyses, suggested a stable population size in the structured Lineage A and a rapid range expansion for the geographically admixed Lineage C. We hypothesized that the two lineages were associated with hosts experiencing different glaciation histories. The lack of host specificity in L. agilis lineages was in contrast to the co-occurring highly host-specific lineages of Polyplax serrata lice, sharing Apodemus hosts. The incongruence was attributed to the differences in mobility between the parasites, allowing mites to switch hosts more often.
Keywords: Demographic history; Host specificity; Laelaps agilis; Phylogenetic relationship